Establishing a genetic link between FTO and VDR gene polymorphisms and obesity in the Emirati population - Khan, Saad Mahmud (BMC Med Genet, 2018)
BACKGROUND: Obesity is a metabolic disease that is widely prevalent with approximately 600 million people classified as obese worldwide. Its etiology is multifactorial and involves a complex interplay between genes and the environment. Over the past few decades, obesity rates among the Emirati population have been increasing. The aim of this study was to investigate the association of candidate gene single nucleotide polymorphisms (SNPs), namely FTO (rs9939609) and VDR (rs1544410), with obesity in the UAE population. METHODS: This is a case-control study in which genomic DNA was extracted from saliva samples of 201 obese, 115 overweight, and 98 normal subjects in the United Arab Emirates (UAE). Genotyping for the variants was performed using TaqMan assay. RESULTS: The mean Body Mass Index (BMI) ± SD for the obese, overweight, and normal subjects was 35.76 ± 4.54, 27.53 ± 1.45, and 22.69 ± 1.84 kg/m(2), respectively. Increasing BMI values were associated with increase in values of HbA1c, systolic and diastolic blood pressure. There was a significant association observed between the FTO SNP rs9939609 and BMI (p = 0.028), with the minor allele A having a clear additive effect on BMI values. There was no significant association detected between BMI and rs1544410 of VDR. Moreover, significant interaction between the FTO rs9939609 and physical activity reduced the “AA” genotype effect on increase in BMI (p = 0.027). CONCLUSIONS: Our study findings indicate that the minor allele A of the rs9939609 has a significant association with increasing BMI values. Moreover, our findings support the fact that increasing BMI is associated with increasing risks of other comorbidities such as higher blood pressure, poorer glycemic control, and higher triglycerides. In addition, physical activity was found to attenuate the effect of the “AA” genotype on the predisposition to higher BMI values.